Next-generation thinking. (Economist, 2018)
The article discusses a memo from an official at the U.S. National Security Council who urged the government to build and run 5G as the next generation of mobile network. The memo wanted to protect the network from Chinese hacking. Experts and regulators dismissed the proposal because it would affect competition in the telecommunication industry and raise the risk of overreach by government security agencies.